The Holocaust & The Exile of Yiddish: A History of the Algemeyne Entsiklopedye. Barry Trachtenberg - Veidlinger, Jeffrey (Holocaust and genocide studies, 2023)
Encyclopedias were all the rage in the early twentieth century. European cultures shared the belief that human knowledge could be distilled and disseminate